Biophysical and functional studies of neurotensin receptor 1 - Lavington, S (2020)
G protein coupled receptors (GPCRs) are a large family of membrane proteins that facilitate diverse cellular signalling processes and represent significant drug targets. There has been considerable progress in understanding the molecular process of GPCR activation, but structural, biophysical & functional studies of GPCRs typically make use of a small number of well-studied receptors, sometimes with heavily modified sequences and often in the absence of the lipid environments in which GPCRs have evolved to be functional. In this thesis, the neurotensin receptor 1 (NTS1) is used as a model GPCR to explore aspects of receptor dynamics and function, with emphasis on the use of minimally modified receptor sequences. Firstly, using site-specific cysteine mutants and an E. coli expression system, the conformational dynamics of the proximal C-terminus of NTS1 were defined for the receptor in a native-like lipid environment, resolving a literature dispute concerning the structure of ‘helix 8’ for NTS1. Secondly, production of NTS1 and the heterotrimeric G proteins Gq and Gi1 was established using insect cell expression systems, and high-quality native mass spectra were obtained for NTS1 that demonstrate receptor palmitoylation, and pave the way for the study of post-translational modifications of GPCRs by native mass spectrometry. Thirdly, using a GTP turnover assay, lipids were identified which selectively enhanced NTS1-Gq over NTS1-Gi1 coupling, suggesting a role for membrane composition in selectivity of NTS1 signalling. Finally, the novel polymethacrylate (PMA) amphipathic polymer was used to establish detergent-free purification of NTS1, representing the first detergent-free purification of any membrane protein using PMA. The work presented here thus progresses the field, both in terms of our molecular understanding of GPCR signalling and in terms of technical advances that will facilitate further studies.